Anomalous behaviour of X-ray absorption observed on the highly correlated cerium nitride (CeN) compound - Kappler, J.P.; Beaurepaire, E.; Krill, G.; Sereni, J.G.; Godart, C.; Olcese, G.L.; Sereni, Julián (EDP Sciences, 1991)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Université de Nancy; Francia